2020
DOI: 10.18260/3-1-1153-36021
|View full text |Cite
|
Sign up to set email alerts
|

Worked Example Videos for Blended Learning in Undergraduate Engineering

Abstract: Blended learning is becoming increasingly prevalent in engineering education due to its flexibility and enhanced learning outcomes, however it can face challenges in maintaining student engagement and satisfaction. This study investigates the impact of worked example videos (WEVs) as a blended learning approach within undergraduate engineering, addressing a gap in the literature around their impact as a self-directed study tool in large semester-long courses. WEVs were evaluated using a mixed methods approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 28 publications
(40 reference statements)
3
12
0
Order By: Relevance
“…Under the advocacy of the MOE, colleges and universities actively build online resources or introduce them for use in BL. Attempts of BL in other countries have involved the use of teacher-developed resources such as worked example videos or screencasts with low production requirements but with satisfactory effects (Ahmad et al, 2013;Dart et al, 2020), or those sourced from various social media outlets. However, the MOE has imposed strict technical standards and a high level of quality requirements for online courses, including those regarding video resolution, embedded subtitles and tests.…”
Section: Context Of the Studymentioning
confidence: 99%
“…Under the advocacy of the MOE, colleges and universities actively build online resources or introduce them for use in BL. Attempts of BL in other countries have involved the use of teacher-developed resources such as worked example videos or screencasts with low production requirements but with satisfactory effects (Ahmad et al, 2013;Dart et al, 2020), or those sourced from various social media outlets. However, the MOE has imposed strict technical standards and a high level of quality requirements for online courses, including those regarding video resolution, embedded subtitles and tests.…”
Section: Context Of the Studymentioning
confidence: 99%
“…Furthermore, providing WEVs as a supplement means instructors are not required to redevelop existing classroom materials or upskill in new classroom facilitation techniques. There is evidence WEVs facilitate active learning directly through students solving problems alongside the videos (Dart, Pickering, et al, 2020;Martin, 2016). This personal agency and voluntary nature of the interactions can mitigate against student resistance, addressing a further barrier to implementation for instructors.…”
Section: Blended Learning Designsmentioning
confidence: 99%
“…Other aspects of WEVs that have been investigated include student approaches to and motivations for engagement. Both Dart, Pickering et al (2020) and Martin (2016) showed that engineering students frequently solved problems presented in WEVs, with students often pausing to work ahead, and then restarting the videos to get hints when stuck or to verify solutions. Students also described replaying sections of WEVs to fully comprehend the reasoning behind the problem-solving process.…”
Section: Previous Studies Of Wevs In Higher Educationmentioning
confidence: 99%
See 2 more Smart Citations